Strategi Pemasaran Pariwisata Dan Manajemen SDM Berbasis Kearifan Lokal Dalam Penguatan atribut Produk Pariwisata Kecamatan Kabila Bone Kabupaten Bone Bolango - Ahmad, Muchtar; Radji, Djoko Lesmana; Saman, Siti Nur A. (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2025)
The purpose of this study is to find out the Tourism Marketing Strategy and Human Resources Management in Improving the Creative Economy Based on Local Wisdom Strengthening the Attributes of Local Tourism Products in Kabila Bone District, Bone Bolango Regency. The research method used is a quantitative research method with multiple regression. The results of the research show that in terms of tourist attraction attractions, Kabila Bone District, Bone Bolango Regency according to visitor responses are in the attractive category, tourist attraction facilities are in the inadequate category, while the accessibility of beach tourist attractions is in the category of quite available. Human resource management (managers) will have a positive impact on the value of trust in visitors to tourist attractions (attractions, facilities and accessibility). If it is improved again, it will be better to present attractions that will provide increased customer value. From the aspect of local wisdom, it is necessary to strengthen the education of the surrounding community to understand the visit of foreign tourists to enjoy Susana Beach. Facilities have an impact on customer value, meaning that the better the provision of facilities, the more customer value will increase. And accessibility also has an impact on customer value, meaning that the better the provision of accessibility will provide increased customer value, so that it will increase the economic income of the community, especially the management of beach tourist attractions. With the value of excellence increasing visitors obtained from the value of benefits is relatively better, but seen from the category of both the value of benefits and the value of sacrifices are included in the good category of determining the superiority of the beach tourist attraction of Kabila Bone District, Bone Bolango Regency.